2021
DOI: 10.1097/wno.0000000000001294
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Increased Emergency Department Utilization in Patients With Acute Optic Neuritis

Abstract: Background: Symptoms of acute vision loss and eye pain may lead patients with optic neuritis to seek care in the emergency department (ED). Given the availability of lower cost alternatives for providing medical care for optic neuritis, this study aimed to identify factors associated with higher ED utilization. Methods: Subjects with acute optic neuritis were identified through a chart review of adults with International Classification of Diseases-9 (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In fact, 110 (44%) had confirmed alternative diagnoses. For the cohort with optic nerve enhancement, our group previously reported that the most predominant alternative etiologies were neoplasm or lesions, followed by other optic neuropathies (13). For the cohort without enhancement, other etiologies were predominantly other optic neuropathies, followed by neoplasms or other lesions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, 110 (44%) had confirmed alternative diagnoses. For the cohort with optic nerve enhancement, our group previously reported that the most predominant alternative etiologies were neoplasm or lesions, followed by other optic neuropathies (13). For the cohort without enhancement, other etiologies were predominantly other optic neuropathies, followed by neoplasms or other lesions.…”
Section: Discussionmentioning
confidence: 96%
“…MRI was classified as positive for acute optic neuritis if there was gadolinium-contrast enhancement of the optic nerve noted on the MRI report and otherwise classified as negative. Subjects with positive MRI are the same as those in our previously published study (13). Subjects with negative MRI have not been previously reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ICD codes are a convenient source of big data, in isolation they are not guaranteed to provide an acceptable level of accuracy for use in neuro-ophthalmic research. Previous studies (9,(35)(36)(37)(38)(39)(40)(41) have used ICD codes to collect cases worthy of further review, followed by a time-intensive medical record review by the investigators to accurately identify cases that meet inclusion criteria. However, this level of manual review may not be compatible with an eventual goal of using big data to exponentially increase the number of research subjects or even possible the big data source is not linked to clinical records.…”
Section: International Classification Of Diseases Codesmentioning
confidence: 99%
“…ON can often be first clinically observed in the Emergency Room (ER). 3 Once that a major challenge is that the prognosis and the therapeutic strategy can differ according to the mechanism involved, the initial work-up is fundamental to determine the specific cause, efficient diagnostic assessment and appropriate therapeutic strategy. 1,2,4 In what concerns the clinical history and examination, ON can present with diverse neuro-ophthalmological findings,and vision loss may be preceded or simultaneous to eye pain/discomfort.…”
Section: Introductionmentioning
confidence: 99%